Pembentukan Karakter Religius Melalui Pembiasaan Shalat Berjamaah - Yeni Yuliana (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
Character is a set of traits that contain a person's goodness, virtue and moral maturity. Character is formed through habits that are carried out repeatedly by a person. If someone often behaves well then that person's character is also good. Getting into the habit of praying in congregation is a form of habituation for a person to get closer to his Creator. The formation of religious character in individuals is one of the influences of the values contained in congregational prayer. The purpose of this writing is to find out how effective the influence of congregational prayer is in forming an individual's religious character. Observation and literature review via the internet are data collection techniques used in this research. The results of the research show that getting used to praying together can improve a person's religious character.